Determinants of smallholder commercialization of food crops: Theory and evidence from Ethiopia - Pender, John L.; Alemu, Dawit (International Food Policy Research Institute, 2007)
In this paper, we develop a theoretical farm household model of food crop production and marketing decisions, derive testable hypotheses concerning the determinants of these decisions, and test these hypotheses, using data on cereal production and marketing collected from a nationally representative survey of 7,186 farm households in Ethiopia. Focusing on production and marketing decisions for teff and maize, the two most important crops in Ethiopia, we find that most producers of these crops are either autarkic or net buyers (especially for maize) and that net buyers and autarkic households are poorer in many respects than net sellers. This implies that interventions to increase cereal productivity will favorably affect distribution for most producers. The econometric analysis shows that increasing production of teff and maize is the most important factor contributing to increased sales, and that increased smallholder access to roads, land, livestock, farm equipment, and traders is key to enabling increased smallholder production and commercialization of these crops.